Gene flow and genetic drift contribute to high genetic diversity with low phylogeographical structure in European hoopoes (Upupa epops) - Wang, Erjia; Wijk, Rien E. van; Braun, Markus S.; Wink, Michael (Molecular phylogenetics and evolution, 2017)
The Hoopoe (Upupa epops epops) breeds widely in Eurasia and most populations migrate to Africa during the boreal winter. To date, data regarding its phylogeography in Europe are missing. In this study, we investigated the phylogeography and population genetics of Hoopoes by means of mitochondrial DNA (mtDNA) sequencing as well as microsatellite genotyping. Our analyses revealed 32 haplotypes in the cytochrome c oxidase subunit I (COI) (269 individuals) and 50 haplotypes in cytochrome b (cyt b) (233 individuals). Analyses of mtDNA clearly demonstrated that the bulk of variance (98.23%) could be attributed to inner-population variance. Thus, the low frequency single nucleotide substitutions resulted in “star-like” haplotype networks without define geographical structure. Hoopoes clearly experienced a bottleneck followed by sudden expansion, as was also apparent from tests on the unimodal mismatch, Bayesian skyline plot, significant negative neutrality tests as well as bottleneck signals. These tests pointed to strong demographic fluctuations in the hoopoe populations. GENELAND, DAPC and STRUCTURE analyses of microsatellites along with their corresponding Fst values suggested that current genetic restriction separates birds from Armenia from the remaining populations. Except for hoopoes from Armenia, all the European populations exhibited an admixed phylogeographic pattern. We conclude that this genetic panmixia might be a consequence of a combination of historical events (e.g. repeated colonizations and retreatments from northern habitats during the Pleistocene and a sudden postglacial expansion) and current processes (e.g. long-distance migration, immigration or population recruitments).
Gesehen am 31.07.2017